Analysis on full CO2 capture schemes in NG/O2 combustion gas and steam mixture cycle (GSMC). (15th January 2020) - Wu, Jiafeng; Chen, Yaping; Zhu, Zilong; Zheng, Shuxing
Abstract: The nature gas and pure oxygen (NG/O2) combustion gas and steam mixture cycle (GSMC) is a novel power generation cycle using NG/O2 combustion product and circulation H2O as the turbine working medium, which can implement efficient power generation, CO2 capture and energy shifting. In GSMC, cold energy of liquefied natural gas (LNG) and liquefied oxygen (LO2) is used for CO2 capture. The CO2 capture schemes are analyzed to improve the CO2 capture as well as the system efficiency. The main means to increase the CO2 capture and extend CO2 full capture range include the reduction of CO2 liquefaction enthalpy drop and the conservation of cooling energy consumption in CO2/moisture separation. Lower efficiency is always a penalty of the full CO2 capture especially with higher condenser outlet temperature. The optimal scheme is different under different conditions such as parameters of turbine inlet, cooling water, and CO2 liquefaction. At turbine inlet of 30MPa/1000 °C and condenser outlet of 18kPa/38 °C, the efficiency drop is 1.18% for the full CO2 capture of the improved scheme, while the CO2 capture ratio of the original GSMC scheme is less than 60%. The distinctive CO2 capture of GSMC is summarized as system indispensable, scheme optional and method promotable. Highlights: Schemes are designed and discussed for full CO2 capture of the novel GSMC system. Separation of CO2/H2O moisture is further considered and re-planed in new schemes. Efficiency penalty with full CO2 capture increases at high ambient temperature. Efficiency drop is 1.18% at proper design to raise CO2 capture from 60% to 100%. CO2 capture reformation in power plant with GSMC system is of great significance.